Impact of COVID-19 pandemic on clinical and embryological outcomes of assisted reproductive techniques - Manish Banker; Parul Arora; Jwal Banker; Anand Shah; Reena Gupta; Sandeep Shah (Wolters Kluwer Medknow Publications, 2022)
Background: The emergence of the COVID pandemic unfolded a series of precautions and dilemmas and the complete suspension of health services. With the gradual emergence of data showing near minimal effects of the virus on pregnancy, Assisted Reproductive Techniques (ART) services were gradually resumed following guidelines and advisories. Aim: The purpose of this study was to detect the COVID positivity rate in women undergoing ART treatment during the COVID pandemic and compare clinical and embryological outcomes to the ART cycles performed in the pre-COVID era. Study Design and Settings: This was a retrospective cohort study of all women undergoing controlled ovarian stimulation, followed by a fresh or frozen embryo transfer (ET) between 1st October 2019 and 31st March 2020 (control group) and between 1st April 2020 and 31st September 2020 (study group) at Nova IVF Fertility Clinic, Ahmedabad. Material and Methods: The study group underwent ART during the first wave of COVID-19 pandemic in India and when gradual unlocking of facilities including ART was advised as per the national ART advisory by the ICMR in December 2020. The outcomes were compared with the control group (cycles in pre-covid time). Statistical Analysis: Statistical analysis was performed in SPSS (v25.0) and included Mann-Whitney U, Fisher's exact and Pearson Chi-square as appropriate. Values of P < 0.05 were considered statistically significant. Results: A total of 367 in vitro fertilisation (IVF) stimulations were initiated. A total of 342 retrievals and 606 ETs (171 fresh and 435 frozen) were completed during the study period with a COVID positivity rate of 6.8% (25/367) amongst fresh and 3.9% (18/453) amongst frozen ETs, respectively; the PR and IR in the study group was similar to the control group (47.6 vs. 55.1 P = 0.4 and 68.7 vs. 66.4; P = 0.52, respectively). The maternal complication rates were similar in both groups with a COVID positivity rate of 10.2% (23/225) and 1 maternal death in the study group. The live birth rates were similar. Conclusions: We did not find a noteworthy difference in the clinical and embryological outcomes in the IVF cycles conducted in the COVID era as compared to the pre-COVID time. Thus, with adequate precautions and safety measures, ART services conducted during the COVID pandemic have comparable birth outcomes and can be safely advocated.